BEING MACHIAVELLIAN, NARCISSISTIC, AND “PSYCHOPATHIC” MAKES YOU DEPRESSED? DARK TRIAD TOWARDS DEPRESSIVE SYMPTOMS DURING THE PANDEMIC - Nathan Andhikaputra Sie; Yuliana Anggreany (MANASA, 2022)
People all over the world have suffered in numerous ways due to the now occurring Covid-19 pandemic. The virus not only impacts the physical health, but psychological health as well. People, especially emerging adults with their period of financial and emotional instability, are now more vulnerable to suffer from psychological disorders, such as depression. The dark triad personality traits are socially aversive personality traits. The dark triad personality traits consist of Machiavellianism, psychopathy, and narcissism. Understanding that personality affects the onset of depression, the researcher examines the role dark triad personality traits has towards depression and its symptoms in this current Covid climate. This research used a sample of 130 participants recruited through online questionnaires. The research participant used in this research are emerging adults ranging from ages 18-25 living in Jabodetabek. The findings show that Machiavellianism and psychopathy are positively correlated and influences the prevalence of depressive symptoms within the sample by 12.8% and 14.1%. Narcissism showed no significant correlation with depressive symptoms.